Legal Review Enforcement Repressive Legal Efforts Against Narcotics Users Of Children - Alfredo Risano; Ayu Dian Ningtias (Universitas Islam Lamongan, 2021)
In terms of enforcement the law. Second, legal instruments in the framework of criminal law enforcement abuse of narcotics against minors using a legal basis Law Number 11 of 2012 concerning the Criminal Justice System for Children. In the the provisions of the SPPA Law, in order to prosecute children who are involved with the law, then a diversion effort is carried out, namely a restorative effort or recovery state solve the problem together, in this research is focous about How are repressive legal measures against child narcotics users in under age?. As previously explained, in act Number 11 In 2012 concerning the Juvenile Criminal Justice System, there is a restorative principle (Restorative justice), which is aimed at restoring the original state, meaning efforts to restore the attitudes and mentality of children who have committed acts the crime of narcotics abuse to be as before or as a cure for the criminal act he has committed. Of course, the provisions of the Narcotics Law are not sidelined even though his repressive legal remedies are based on the provisions of law SPPA.